2018
DOI: 10.1101/335109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Meta-Analysis of Executive Functions in Frontal Cortex: Comparing Healthy and Neuropsychiatric Groups

Abstract: BackgroundThe neural architecture of executive functions remains a topic of considerable clinical and academic interest in the clinical neurosciences, given its strength as a transdiagnostic predictor of adaptive functioning with high heritability. In recent years, meta-analyses have shown a consistent relationship between prefrontal cortex size and executive functioning task performance in healthy adults and lesion patients, with increases in measures of cortical size (i.e., volume or thickness) associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Although NKI-RS is demographically and socioeconomically generalizable to the United States, the contribution of this study to clinical neuropsychology is predicated on such brain–behavior relationships operating in both clinical and nonclinical samples. In accordance with the validation of the D-KEFS in lesion studies, the modest effect sizes for EF and frontal volume found in this study are expected to be stronger in neuropsychiatric populations (Waters, Swenson et al, 2018). It is possible that additional EF–frontal associations were not detectable in this sample of community-dwelling adults (Type II error).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although NKI-RS is demographically and socioeconomically generalizable to the United States, the contribution of this study to clinical neuropsychology is predicated on such brain–behavior relationships operating in both clinical and nonclinical samples. In accordance with the validation of the D-KEFS in lesion studies, the modest effect sizes for EF and frontal volume found in this study are expected to be stronger in neuropsychiatric populations (Waters, Swenson et al, 2018). It is possible that additional EF–frontal associations were not detectable in this sample of community-dwelling adults (Type II error).…”
Section: Discussionsupporting
confidence: 88%
“…dance with the validation of the D-KEFS in lesion studies, the modest effect sizes for EF and frontal volume found in this study are expected to be stronger in neuropsychiatric populations (Waters, Swenson et al, 2018). It is possible that additional EF-frontal associations were not detectable in this sample of communitydwelling adults (Type II error).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although NKI-RS is demographically and socioeconomically generalizable to the US, the contribution of this study to clinical neuropsychology is predicated on such brainbehavior relationships operating in both clinical and non-clinical samples. In accordance with the validation of the D-KEFS in lesion studies, the modest effect sizes for EF and frontal volume found in this study are expected to be stronger in neuropsychiatric populations (Waters, Swenson, & Gansler, 2018).…”
supporting
confidence: 88%